Effects Of Hydrolysis Using Various Parameter For Recovery Of Reducing Sugar From Local Coconut Dregs - Mohd Amir, Esmanizam Esmaly Eusainy (Universiti Sains Malaysia, 2018)
The coconut dregs one of the source to create alternative fossil fuel that could help reduce a lot of environmental problems. The content of carbohydrates of cellulose and hemicellulose inside coconut dregs can be hydrolyzed to produce bioethanol and also reducing agent for metallurgical industries. The aim of this study is to understand and investigate the hydrolysis of coconut dregs. First, physical characterization study was done to study their alteration on surface morphology after best of delignification and all indirect acid hydrolysis was done. Next, the pretreatment of coconut dregs was done by comparing acid and alkali pretreatment and acid solution was selected as the best pretreatment solution at condition of using 6g of coconut dregs immersed in 100mL of 0.5% of H2SO4 solution at 70˚C for 2 hours, which gives 9.33% weight loss and 0% glucose yield. Next, the best of indirect and direct hydrolysis outcome shows that indirect acid hydrolysis has higher weight loss and glucose yield compared to direct acid hydrolysis. And the final conditions that is yielding highest weight loss and glucose yield is by first doing pre-treatment as in best of pre-treatment condition and continued process to the best of all parameter with conditions of, 6g of coconut dregs after pre-treated immersed in 100mL of 3% concentration fresh acid solution at 90˚C for 2 hours and have total of 4 hours for indirect acid hydrolysis. The Glucose content was determined by using DNS calorimetry method analyzed using UV-Visible spectrometry and give the highest yield of 1.263g/L with best of indirect acid hydrolysis condition.